Immunohistochemical Profile and Distribution of Non-Hodgkin and Hodgkin Lymphoma - An Experience in a Medical College Hospital in Tamil Nadu - Shanmugasundaram, Sakthisankari; Balan, Krishnagiri; Arumugam, Dhanalakshmi (Indian Journal of Medical and Paediatric Oncology, 2020)
Context: The subtype distribution of non-Hodgkin lymphoma (NHL) and Hodgkin lymphoma (HL) shows distinct pattern across geographic regions. This study analyzes the subtype distribution of lymphomas based on the WHO 2017 Classification using immunohistochemistry (IHC) and also investigates the IHC profile of various lymphomas. Subjects and Methods: Fifty consecutive cases of lymphoma diagnosed in the department of pathology in a medical college hospital were included in the study. The cases were subcategorized using panels of IHC based on the light microscopic findings. Results: The ratio of NHL to HL was 4.5:1. B-NHL formed 78.5% (n = 32), while T-cell NHL formed 21.5% (n = 9). Among the B-NHL cases, small lymphocytic lymphoma/chronic lymphocytic leukemia (SLL/CLL) (34.4%) was the most common, followed by diffuse large B-cell lymphoma, NOS (DLBCL NOS) (31.2%), follicular lymphoma (FL) (25%), and then by Burkitt's lymphoma (BL) constituting 9.4%. Peripheral T-cell lymphoma, NOS (PTCL NOS) (14.1%) (n = 6) was the most common T-cell NHL, followed by angioimmunoblastic T-cell lymphoma (4.8%), and then by lymphoblastic lymphoma (T-LL) (2.4%). Among Hodgkin lymphomas, mixed cellularity (MC) accounted for 55.6% (n = 5), lymphocyte depleted type (LD) being 22.2%, while nodular lymphocyte predominant and lymphocyte rich type each constituted 11.1%. Conclusion: SLL/CLL was the most common lymphoma reported in the study followed by DLBCL which is different from the other Indian studies where DLBCL was most common. CD5 expression was noted in 21% of FLs. PTCL-NOS constituted the most common T-cell lymphoma and MC, the most frequent subtype of classical HL. Further replication studies including larger sample size will be needed to understand the difference in subtype distribution in our population.
Keywords: CD5; Hodgkin lymphoma; immunohistochemistry; Lennert's lymphoma; non-Hodgkin lymphoma; small lymphocytic lymphoma